The Role of Food Supplementation in Microcirculation—A Comprehensive Review - Raposo, António (Biology (Basel), 2021)
SIMPLE SUMMARY: There is increasing evidence showing that the pathophysiology of several forms of cardiovascular disease (CVD) are characterized by microcirculatory dysfunction, which may in fact precede clinical manifestations. For several decades, food supplements have been explored with the aim of restoring microcirculation. Considering the increasing growth of the food supplement industry in recent years and the great impact that CVD has on human health, the present study aimed to provide an up-to-date review of the literature on the role of food supplementation in microcirculation. In this work, the main legal aspects in the European Union and the United States of America concerning food supplements and the beneficial effects that these supplements may have on the population for microcirculation are discussed. Although further studies are needed, especially in humans, there are some data that suggest the beneficial effect of the following supplements: Ruscus aculeatus L., Centella asiatica L., Ginkgo biloba L., Salvia miltiorrhiza Bunge, Crataegus spp., Ginseng, Mangifera indica L., Aesculus hippocastanum L., Hamamelis virginiana L., and Vitis vinifera L. ABSTRACT: (1) Background: Cardiovascular disease (CVD) is a major public health concern worldwide and a key cause of morbidity and mortality in developed countries. Accumulating evidence shows that several CVD forms are characterized by significant microcirculatory dysfunction, which may both cause and be caused by macrovascular disease, often preceding clinical manifestations by several years. Therefore, interest in exploring food supplements to prevent and restore microcirculation has grown. Given the continuous need to expand the available therapeutic arsenal for CVD, the food supplements market has recently grown and is expected to continue growing. (2) Methods: We provide an authoritative up-to-date comprehensive review of the impact of food supplementation on microcirculation by analyzing the European and American legal food supplements framework and the importance of food safety/food quality in this industry. We review the main literature about food bioactive compounds with a focus on microcirculation and some main food supplements with proven benefits. (3) Results: Despite a lack of scientific evidence, diet and microcirculatory function are clearly connected. The main food supplement examples in the literature with potential beneficial effects on microcirculation are: Ruscus aculeatus L., Centella asiatica L., Ginkgo biloba L., Salvia miltiorrhiza Bunge, Crataegus spp., Ginseng, Mangifera indica L., Aesculus hippocastanum L., Hamamelis virginiana L., and Vitis vinifera L. (4) Conclusions: further clinical trials are necessary to better explore the effects of these food supplements.